Role of the sonographic assessment of fluid estimate score on evaluating intravascular volume status in critically ill patients - Raja, Bhuvaneswari; Sada, Chethan; H. R., Hemant (International Journal of Research in Medical Sciences, 2024)
Background: Study aim to establish standardized scoring system using bedside ultrasonography to evaluate intravascular volume status in critically ill patients and to correlate this with traditional physician assessment methods. Methods: A prospective pragmatic observational study was conducted at Narayana health city from August 2021 to February 2022, involving 100 adult medical ICU patients requiring volume status assessment. Patients with local infection, trauma, or increased intra-abdominal pressure were excluded. Volume status was categorized as hypovolemic, euvolemic, or hypervolemic using both the intensivist’s methods and the sonographic assessment of fluid estimate (SAFE) score. The agreement between these methods was analyzed. Results: The SAFE score showed a high agreement with the physician’s assessment methods, with a Kappa value of 0.91. The SAFE score demonstrated sensitivity of 100 % and specificity of 100% for identifying hypervolemic (score>1) and (score≤-1) for patients with hypovolemia, both with 100% positive and negative predictive values. For euvolemic patients, the SAFE score had 57.47% specificity, a 26% PPV, and a 100% NPV. Subgroup analyses, including mechanically ventilated patients, those with ARDS, vasopressor requirements, and septic shock, confirmed statistically significant agreement between the two methods. Conclusions: The SAFE score is a reliable, non-invasive, cost-effective, and time-efficient method to assess volume status in critically ill ICU patients. It offers a standardized alternative to traditional assessment techniques, with specific thresholds indicating hypovolemia (>-2), hypervolemia (> 2), and euvolemia (-1 to 1).